Konseling Multikultural: Upaya Preventif Bullying pada Lesbian di Masyarakat dan Sekolah - Harahap, Nurintan Muliani; Maryolo, Amril (IAIN Palopo, 2018)
The objectives of this paper are to neutralize cases of bullyingto minority groups, especially lesbians in communities and schoolsusing multicultural counseling. In general, people consider lesbians as sinners, sexual deviations and sexual disorders. This group frequently experience discrimination and stigma. The problem faced by this sexual orientation or gender identity group requires empathy and sensitivity. Therefore, all problems can be solved. One of the problems experienced by LGBT especially lesbians is bullying. Forms of intimidation and logging from the nearest person and others commonly referred to as bullying behavior. In order to end the behavior, supporting and minority group outreachingshould be conducted according to the groupsâ potential.